Comparison of reading achievement through a standarized test and the evaluation of the teacher - Pujol, Lydia (1998)
A comparison of reading achievement assessed by an standarized reading test with the prevalence estimated by the teachers was performed, by calculated agreement in a sample of 520 elementary school children in Caracas, Venezuela. Reading Achievement was defined as the ability to understand and use those forms of written language required by society and/or valued by the individuals. The prevalence of reading difficulties obtained from test scores was 15 % and that obtained by the estimation made by teacher was 40 %. A moderate agreement between measured was obtained and a tendency of the teachers to understimate reading achievement was evidenced when compared with the results of the test. Implications of results are discussed.